(untitled) (American Journal of Islam and Society, 2014)
This rare publication on Islamic art and architecture revolves around a clear conceptual idea. A plethora of broad and specific survey texts continue to be published; however, very seldom does a thematic book come along with a thorough look at one idea. The collection is composed of an introduction, a port- 128 The American Journal of Islamic Social Sciences 31:2 folio, and ten essays. As with many compilations, the essays are not all of the same caliber and there are some structural issues. And yet the whole is a refreshing look at the theme of jannat (paradise) in Islamic art and architecture in the Indian subcontinent. Not only are several historical eras encompassed, but the important connection to contemporary artistic expressions is also made. Mumtaz Currim’s introduction succinctly discusses the themes covered. His excellent summary of the philosophical and cosmological concepts of paradise in relation to the garden is followed by a clear account of the chahar bagh (quad-partite garden) and the Mughal legacy of gardens as microcosms of paradise. The relationship of water to both gardens and paradise are reflected upon with respect to engineering and the expressions in textile art. The section concludes with a look at paradise in literary works and popular art. The portfolio includes beautiful reproductions of two very different groups of calligraphic art. The first collection is from the twelfth- to sixteenthcentury manuscript Qur’ans in Hyderabad’s Salar Jung Museum. The selected verses refer to paradise, such as those found in the chapters of al-Fātiḥah (The Opening), al-Raḥmān (The Merciful), and al-Wāqi‘ah (The Event). The manuscripts’ calligraphy, as well as their geometric and arabesque elaborations, are vividly reproduced in the color images. The second collection consists of contemporary artworks by Salwa Rasool, who uses canvas, vellum, leather, and other materials to focus on the Names of Allah and Sūrat al-Fātiḥah’s, chapter and religious phrases. With very little accompanying text, aside from the notation of details, the reader is introduced to the concept of paradise through the sheer beauty of the Qur’an’s textual descriptions and the word’s evocative role. The juxtaposition of historical and contemporary works reveals the continuity of the concepts in Islamic cultures ...